2010
DOI: 10.1177/0170840610376147
|View full text |Cite
|
Sign up to set email alerts
|

Institutional, Industry and Power Effects on Integration in Cross-border Acquisitions

Abstract: Drawing on comparative institutional theory, this paper examines post-acquisition integration in international acquisitions, which has seldom been examined through this perspective. Based on a longitudinal and comparative study of three blue-chip French acquirers in the UK that shared similar integration intentions but realized those to varying degrees, this paper theorizes this variation in integration outcomes as a dynamic interplay of institutional distance, market structure and power dependencies. Whilst a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…), contingent upon the asset management strategy applied (Daniliuc et al . ), as well as the degree to which the firms depend on each other (Mtar ). A pre‐deal alliance between acquirer and target is only positive when the target is loosely integrated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…), contingent upon the asset management strategy applied (Daniliuc et al . ), as well as the degree to which the firms depend on each other (Mtar ). A pre‐deal alliance between acquirer and target is only positive when the target is loosely integrated.…”
Section: Resultsmentioning
confidence: 97%
“…Ranft and Lord (2002) found that differences in size and performance limit communication between the firms involved in an integration, increase the autonomy of the smaller firm and improve employee retention. Regarding market relatedness, overlaps between the firms involved seem to benefit integration success (Ellis et al 2009), contingent upon the asset management strategy applied (Daniliuc et al 2014), as well as the degree to which the firms depend on each other (Mtar 2010). A pre-deal alliance between acquirer and target is only positive when the target is loosely integrated.…”
Section: Contextmentioning
confidence: 99%
“…Continuing the heterodox tradition of Organization Studies , there have remained a few studies which have proposed alternative conceptions of institutions based on entirely different theoretical traditions such as actor network theory (Czarniawska, 2009), comparative institutional theory (Mtar, 2010), studies of total institutions (Clegg, e Cunha, & Rego, 2012), process theory and notions of becoming (Bjerregaard & Jonasson, 2014) and Luhmann’s systems theory (Deroy & Clegg, 2015).…”
Section: A History Of Institutional Theory In Organization Studiesmentioning
confidence: 99%
“…Foreign acquisitions are influenced by country-specific determinants, such as, institutional, regulatory, and political environments, as well as the level of corruption (Xie et al, 2017). The “National Institutional Distance” (NID) between the countries of the acquirers and the target can alter the intended integration strategy, as well as integration outcomes (Kostova, 1999; Mtar, 2010). The incremental costs and risks associated with a target that operates under poor public governance need to be taken into account ex ante, that is, when the firm valuates the target.…”
Section: The Role Of Public Governancementioning
confidence: 99%